Implementation of Civil Rights against Vulnerable Groups in the Legal and Constitutional System in Indonesia - Rudy Rudy; Rudi Natamiharja; Jalil Alejandro Magaldi Serna; Ahmad Syofyan (Hasanuddin Law Review, 2022)
Constitutional Court is established as an effort to uphold the rule of law and provide maximum protection for democracy as well as human rights, particularly civil rights. The main purpose of the rule of law is to protect citizens' freedom from state power. Therefore, this study aims to examine the implementation of civil rights against vulnerable groups in the Indonesian legal and constitutional system. Data were analyzed using a normative juridical approach by examining theories, concepts, legal principles, and statutory regulations obtained from legal sources such as books, articles/writings, and other documents. The government issued various laws and regulations with multiple conventions such as the rights of the child and the elimination of all forms of discrimination but this effort has not been supported by a strong shared commitment. Based on these circumstances, it is necessary to develop an effective law enforcement mechanism to protect citizens' rights, particularly vulnerable groups.